Discovery of DS28120313 as a potent orally active hepcidin production inhibitor: Design and optimization of novel 4, 6-disubstituted indazole derivatives. Issue 23 (1st December 2017) - Fukuda, Takeshi; Goto, Riki; Kiho, Toshihiro; Ueda, Kenjiro; Muramatsu, Sumie; Hashimoto, Masami; Aki, Anri; Watanabe, Kengo; Tanaka, Naoki
Graphical abstract: Abstract: Hepcidin has emerged as the central regulatory molecule in systemic iron homeostasis, and its inhibition could be a favorable strategy for treating anemia of chronic disease (ACD). Here, we report the design, synthesis and structure–activity relationships (SAR) of a series of 4, 6-disubstituted indazole compounds as hepcidin production inhibitors. The optimization study of multi-kinase inhibitor1 led to the design of a potent and bioavailable hepcidin production inhibitor, 32 (DS28120313), which showed serum hepcidin-lowering effects in an interleukin-6-induced acute inflammatory mouse model.